Decision on Suspension of Obligation for Payment of Debt which Ended in Bankruptcy at PT Sarana Yeoman Sembada - Edi Wahjuni; Ayu Citra Santyaningtyas; Jelita Darma (PT Mattawang Mediatama Solution, 2022)
The aim of this research is to find out about the simple evidentiary regulations in Law Number 37 of 2004 concerning Bankruptcy and PKPU. In addition, to find out the formal evidence as well as the judge's legal considerations in the decision to postpone the payment of debt obligations that ended in bankruptcy at PT. Sarana Yeoman Sembada. This research uses normative legal research. The results of this study are that the simple evidence referred to in the determination of bankruptcy is also contained in the PKPU arrangement in Article 222 of the Bankruptcy Law and PKPU. In addition, the Bilyet Giro submitted in the PKPU application against PT. Sarana Yeoman Sembada is invalid as evidence because it does not meet the formal requirements of the Bilyet Giro and violates the provisions contained in the Bankruptcy Law and PKPU, so that the bankruptcy decision given by the Panel of Judges to PT. Sarana Yeoman Sembada was declared wrong because the application which was granted by the Panel of Judges came from an application submitted by the Petitioner who had no legal standing.